Warming alters plankton body-size distributions in a large field experiment - Dania Albini; Emma Ransome; Alex J. Dumbrell; Samraat Pawar; Eoin J. O’Gorman; Thomas P. Smith; Thomas Bell; Michelle C. Jackson; Guy Woodward (Communications Biology)
Abstract The threat of climate change has renewed interest in the responses of communities and ecosystems to warming, with changes in size spectra expected to signify fundamental shifts in the structure and dynamics of these multispecies systems. While substantial empirical evidence has accumulated in recent years on such changes, we still lack general insights due to a limited coverage of warming scenarios that span spatial and temporal scales of relevance to natural systems. We addressed this gap by conducting an extensive freshwater mesocosm experiment across 36 large field mesocosms exposed to intergenerational warming treatments of up to +8 °C above ambient levels. We found a nonlinear decrease in the overall mean body size of zooplankton with warming, with a 57% reduction at +8 °C. This pattern was broadly consistent over two tested seasons and major taxonomic groups. We also detected some breakpoints in the community-level size-temperature relationship, indicating that the system’s response shifts noticeably above a certain level of warming. These results underscore the need to capture intergenerational responses to large gradients in warming at appropriate scales in time and space in order to better understand the effects of warming on natural communities and ecosystems.